New highly polymorphic microsatellite markers for the aquatic angiosperm Ruppia cirrhosa reveal population diversity and differentiation - Martínez-Garrido, J. (2014)
Ruppia cirrhosa is a clonal monoecious plant phylogenetically associated to seagrass families such as Posidoniaceae and Cymodoceaceae. It inhabits shallow waters that are important for productivity and as a biodiversity reservoir. In this study, we developed 10 polymorphic microsatellite loci for R. cirrhosa. Additionally, we obtained cross-amplification for two microsatellites previously described for Ruppia maritima. These 12 markers were tested in four R. cirrhosa populations from the southwest of Europe. The number of alleles per locus was high for most of the markers, ranging from 4 to 13. Two populations (Sicily and Cádiz) showed heterozygote deficit (p < 0.001). The four populations (Sicily, Murcia, Cádiz, and Tavira) were significantly differentiated (FST ≠ 0; p < 0.001), corroborating the usefulness of these microsatellites on R. cirrhosa population genetics.